2015
DOI: 10.3389/fpsyg.2015.00714
|View full text |Cite
|
Sign up to set email alerts
|

10 years of BAWLing into affective and aesthetic processes in reading: what are the echoes?

Abstract: Reading is not only “cold” information processing, but involves affective and aesthetic processes that go far beyond what current models of word recognition, sentence processing, or text comprehension can explain. To investigate such “hot” reading processes, standardized instruments that quantify both psycholinguistic and emotional variables at the sublexical, lexical, inter-, and supralexical levels (e.g., phonological iconicity, word valence, arousal-span, or passage suspense) are necessary. One such instrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
112
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 70 publications
(117 citation statements)
references
References 130 publications
(195 reference statements)
4
112
0
1
Order By: Relevance
“…Sensory simulation gets a boost from emotionality in a figurative context, but not in a literal context, comparable with past rating results (Citron et al, 2015;Jacobs et al, 2015). This suggests that the emotional context leads to a more concrete -more 'embodied' -representation of the metaphorical motion, as compared to the same metaphorical motion occurring in a non-emotional context.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Sensory simulation gets a boost from emotionality in a figurative context, but not in a literal context, comparable with past rating results (Citron et al, 2015;Jacobs et al, 2015). This suggests that the emotional context leads to a more concrete -more 'embodied' -representation of the metaphorical motion, as compared to the same metaphorical motion occurring in a non-emotional context.…”
Section: Discussionsupporting
confidence: 82%
“…We expect an emotional 'boost' in the embodiment of metaphorical language, which would be expressed in an increased reliance on sensorimotor regions (Citron et al, 2015;Jacobs et al, 2015). Alternatively, there may be a main effect of emotional context, in the absence of an interaction effect.…”
Section: Introductionmentioning
confidence: 95%
“…In the last decade, a growing body of research on the relationships between language and affect has shown that the emotional content of words affects comprehension processes, challenging semantic models of word recognition and text comprehension that typically have not considered this important aspect (Jacobs, 2011;Jacobs et al, 2015). More specifically, emotionally laden words are recognized faster and have processing priority when compared to neutral words.…”
Section: Introductionmentioning
confidence: 99%
“…Hierarchical diffusion models explicitly allow to estimate diffusion model parameters for individual participants even if the number of data points per subject is relatively small. This makes hierarchical diffusion modeling an ideal method in fields such as psycholinguistics and reading where it is not always possible to generate a large number of stimuli per experimental condition that require careful matching and multiple controls (e.g., Jacobs et al, 2015). …”
Section: Introductionmentioning
confidence: 99%